Bilateral Vertebral Artery Hypoplasia and Fetal-Type Variants of the Posterior Cerebral Artery in Acute Ischemic Stroke - Hsu, Chung-Fu; Chen, Kuan-Wen; Su, Chun-Hung; Shen, Chao-Yu; Chi, Hsin-Yi (Frontiers in Neurology, 2021)
Unilateral vertebral artery hypoplasia had been considered as a risk factor for posterior circulation infarction. Despite the increasing attention on unilateral vertebral artery hypoplasia, limited studies discussed bilateral vertebral artery hypoplasia ,its influence on stroke and its collateral supply from Circles of Willis. We aimed to identified its characteristics , stroke pattern, unique ultrasonographic and brain image findings.Of 1301 consecutive inpatients diagnosed with acute ischemic stroke from January 2013 to December 2015. Medical and laboratory data and a history of previous stroke or transient ischemic attack were recorded. We enrolled patients received both brain magnetic resonance imaging and sonography exam. Vertebral artery and post cerebral artery analysis were conducted by clinical criteria.466 patients had adequate image data. 8 patients of them met the criteria of bilateral vertebral artery hypoplasia. Their mean age was 62.9±12.1. There were 6 male (75.0%) and 2 female patients (25.0%). High prevalence of hypertension (7/8, 87.5%) was noted.The sonography showed very low flow volume in the net flow volume of vertebral arteries, the average of net flow volume is 28.9±9.7ml/min.A high frequency (6/8;75%) of fetal variant Posterior cerebral artery was founded in this group. The infarction patterns of these patient were all bilaterally, scattered and in multiple vascular territory.In patients with bilateral vertebral hypoplasia, they had unique collateral supply, special stroke pattern and younger stroke onset age. Early recognition and stroke prevention would be critical in clinical treatment.